Oral digoxin effects on exercise performance, K+ regulation and skeletal muscle Na+, K+‐ATPase in healthy humans. (2nd August 2022) - Sostaric, Simon; Petersen, Aaron C.; Goodman, Craig A.; Gong, Xiaofei; Aw, Tai‐Juan; Brown, Malcolm J.; Garnham, Andrew; Steward, Collene H.; Murphy, Kate T.; Carey, Kate A.; Leppik, James; Fraser, Steve F.; et al.
Abstract : Abstract: We investigated whether digoxin lowered muscle Na +, K + ‐ATPase (NKA), impaired muscle performance and exacerbated exercise K + disturbances. Ten healthy adults ingested digoxin (0.25 mg; DIG) or placebo (CON) for 14 days and performed quadriceps strength and fatiguability, finger flexion (FF, 105%peak‐workrate, 3 × 1 min, fourth bout to fatigue) and leg cycling (LC, 10 min at 33% V O 2 peak ${\rm{V}}_{{{\rm{O}}}_{\rm{2}}{\rm{peak}}}$ and 67% V O 2 peak ${\rm{V}}_{{{\rm{O}}}_{\rm{2}}{\rm{peak}}}$, 90% V O 2 peak ${\rm{V}}_{{{\rm{O}}}_{\rm{2}}{\rm{peak}}}$ to fatigue) trials using a double‐blind, crossover, randomised, counter‐balanced design. Arterial (a) and antecubital venous (v) blood was sampled (FF, LC) and muscle biopsied (LC, rest, 67% V O 2 peak ${\rm{V}}_{{{\rm{O}}}_{\rm{2}}{\rm{peak}}}$, fatigue, 3 h after exercise). In DIG, in resting muscle, [ 3 H]‐ouabain binding site content (OB‐Fab ) was unchanged; however, bound‐digoxin removal with Digibind revealed total ouabain binding (OB+Fab ) increased (8.2%, P  = 0.047), indicating 7.6% NKA–digoxin occupancy. Quadriceps muscle strength declined in DIG (−4.3%, P  = 0.010) but fatiguability was unchanged. During LC, in DIG (main effects), time to fatigue and [K + ]a were unchanged, whilst [K + ]v was lower ( P  = 0.042) and [K + ]a‐v greater ( P  = 0.004) than in CON; with exercise (main effects), muscle OB‐Fab was increased at 67% V O 2 peak ${\rm{V}}_{{{\rm{O}}}_{\rm{2}}{\rm{peak}}}$ (per wet‐weight, P  = 0.005; per protein P  = 0.001) and at fatigue (per protein, P  = 0.003), whilst [K + ]a, [K + ]v and [K + ]a‐v were each increased at fatigue ( P  = 0.001). During FF, in DIG (main effects), time to fatigue, [K + ]a, [K + ]v and [K + ]a‐v were unchanged; with exercise (main effects), plasma [K + ]a, [K + ]v, [K + ]a‐v and muscle K + efflux were all increased at fatigue ( P  = 0.001). Thus, muscle strength declined, but functional muscle NKA content was preserved during DIG, despite elevated plasma digoxin and muscle NKA–digoxin occupancy, with K + disturbances and fatiguability unchanged. Key points: The Na +, K + ‐ATPase (NKA) is vital in regulating skeletal muscle extracellular potassium concentration ([K + ]), excitability and plasma [K + ] and thereby also in modulating fatigue during intense contractions. NKA is inhibited by digoxin, which in cardiac patients lowers muscle functional NKA content ([ 3 H]‐ouabain binding) and exacerbates K + disturbances during exercise. In healthy adults, we found that digoxin at clinical levels surprisingly did not reduce functional muscle NKA content, whilst digoxin removal by Digibind antibody revealed an ∼8% increased muscle total NKA content. Accordingly, digoxin did not exacerbate arterial plasma [K + ] disturbances or worsen fatigue during intense exercise, although quadriceps muscle strength was reduced. Thus, digoxin treatment in healthy participants elevated serum digoxin, but muscle functional NKA content was preserved, whilst K + disturbances and fatigue with intense exercise were unchanged. This resilience to digoxin NKA inhibition is consistent with the importance of NKA in preserving K + regulation and muscle function. Abstract : Abstract figure legend Digoxin specifically inhibits Na, K‐pumps in all tissues and in skeletal muscle, and thus could therefore impair cellular Na/K homeostasis, excitability and contractility. In heart failure patients, digoxin binds to and therefore reduces the Na, K‐pump content in skeletal muscle; this lower number of available functional Na, K‐pumps is consistent with an elevated circulating [K] during exercise. We show here in healthy volunteers that oral digoxin intake, which resulted in therapeutic [digoxin], did not reduce the muscle Na, K‐pump content, which was unchanged. However, measures with digibind revealed the total number of Na, K‐pumps was elevated by 8%. Digoxin did not affect either arterial [K] or time to fatigue, during both finger flexion exercise and leg cycling exercise. This indicates a remarkable preservation of skeletal muscle Na, K‐pumps and thus also of circulating [K] and performance during fatiguing, intense exercise challenges. However, one adverse consequence of digoxin was a 4% reduction in muscle strength.